UNDIFFERENTIATED PLEOMORPHIC CARDIAC SARCOMA: THE ADVANTAGES OF PET/CT IN DETECTION OF LOCAL RECURRENCE AND DISTANT METASTASES (CASE REPORT) - D. V. Ryzhkova (Sibirskij Onkologičeskij Žurnal, 2016)
The paper presents a case of a 52-year-old female patient with pleomorphic malignant fibrous histiocytoma/ undifferentiated pleomorphic sarcoma of the left atrium. One year after surgical resection of the primary tumor, microsurgical removal of the right parietal lobe metastatic tumor was performed. PET/CT with 11C-methionine and 18F-FDG performed 2 months after surgical resection of brain metastasis revealed local recurrence of sarcoma in the left atrium and left lateral ventricle metastases. This clinical case demonstrates high diagnostic accuracy of PET/CT with 18F-FDG and 11C-methionine in detecting local recurrence of cardiac undifferentiated sarcoma, however, PET/CT with 11C-methionine appears to be superior to PET/CT with18F-FDG in detecting brain metastasis.